Antioxidant and anti-excitotoxicity effect of Gualou Guizhi decoction on cerebral ischemia/reperfusion injury in rats - ZHANG, SHENGNSAN (Exp Ther Med, 2015)
Stroke is the leading cause of disability in adults and the second most common cause of mortality worldwide. There is currently intense interest in the use of natural products in the treatment of the condition. The aim of this study was to investigate the effect of Gualou Guizhi decoction (GLGZD) on rats subjected to cerebral ischemia/reperfusion injury and the possible mechanisms involved. Cerebral ischemia/reperfusion injury was induced by the middle cerebral artery occlusion method. Ischemic injury was assessed by estimating neurological function and measuring brain infarct volume, and the terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling method was employed to examine ischemia-induced apoptosis. The levels of the antioxidative enzyme superoxide dismutase (SOD) and the concentrations of the non-enzymatic scavenger glutathione (GSH) and malondialdehyde (MDA) were measured to investigate the antioxidant mechanisms. In addition, the levels of excitatory amino acids (EAAs) and glutamate receptor 1 (GluR1) were examined using an automatic amino acid analyzer and immunohistochemical analysis. The administration of GLGZD attenuated the cerebral ischemia/reperfusion injury-induced neural deficits and cerebral infarct volume, reduced the levels of MDA and EAAs (glutamate and aspartate), significantly increased the activity of the antioxidant GSH and notably elevated the activity of SOD. Consistently, GLGZD inhibited ischemia-induced apoptosis and downregulated the expression of GluR1. In conclusion, this study suggested that GLGZD exerts a neuroprotective effect on focal cerebral ischemia/reperfusion injury through the modulation of multiple antioxidant and anti-excitotoxicity pathways.